Donkey power: an accepted yet neglected technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The time has come for donkeys to change their international image, so that the world can acknowledge their true worth. Unlike horses, animals of high status, donkeys have been associated with poverty and second-best, yet in many African and some...